2014
DOI: 10.1515/jqas-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Gasping for air: soccer players’ passing behavior at high-altitude

Abstract: A number of soccer officials have long debated whether to ban soccer games played at high altitude above sea level. This paper explores soccer player's passing behavior when playing at high elevations using Copa Libertadores data. For this, I propose a range of direct indicators when playing at high altitude: the number of total passes, the number of passes in the opposition's half, and the number of successful passes. I also review the effects on the percentage of successful passes and the percentage of succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
1
4
0
1
Order By: Relevance
“…Tucker et al (2004) conditions. This statement coincides with the observations made by Tovar (2014), who reported an increase in the percentage of successful passes made by each player in his half during soccer games above 2500 m.a.s.l in the CONMEBOL Libertadores Cup.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Tucker et al (2004) conditions. This statement coincides with the observations made by Tovar (2014), who reported an increase in the percentage of successful passes made by each player in his half during soccer games above 2500 m.a.s.l in the CONMEBOL Libertadores Cup.…”
Section: Discussionsupporting
confidence: 91%
“…Notwithstanding, we cannot guarantee that altitude will be an advantage for the home team. Nassis (2013) and Tovar (2014) state that the maximum speed of players and their number of goals scored, and mistakes made by goalkeepers leading to goals are not significantly influenced by altitude. Plus, the authors found no differences attributable to altitude in various technical aspects such as total number of passes, number of passes in the rival field, and number of successful passes when comparing matches in the 2013 CONMEBOL Libertadores Cup.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the choice of variables to estimate the expected pass indicator is ad hoc, we perform a forward selection method as done, for instance, in Tovar (2014). The estimation considers all types of passes considered by OPTA (head, chip, long ball, others), the pitch coordinates, distance, and angle.…”
Section: The Estimation Strategymentioning
confidence: 99%
“…The players' skills S , at the team level, can be measured using some aggregation of individual performance indicators such as passes, as done in the past by Anderson and Sally () and Tovar (), among others. Other proxies employed are aggregations of various performance measures—the Opta Index for instance (“a major step” towards measuring a “‘collective’ nature of player performance”—Dawson, Dobson, and Gerrard ).…”
Section: The Modelmentioning
confidence: 99%